A Comparative Institutional Approach to Law and Legal Institutions - Barker, George (Victoria University of Wellington Law Review, 1996)
The late 1980s and early 1990s saw a revolution in economic policy and a transformation of the New Zealand economy. Such events also involved a revolution in legal thought and analysis. This article brings the main elements of this new economic approach to law and policy to a wider audience. It seeks to review the main features of the recent and significant advances that have been made in the economic analysis of organisations and institutions. The article first discusses the fundamental factors which must be recognised as constraints on the ability to secure an ideal society. It then discusses how private arrangements seek to overcome these constraints and the limits to their success. The role of the state in alleviating or overcoming problems with private solutions is also discussed, with the author stressing the need to recognise that the state is not an omniscient and omnipotent solver of social problems. The author concludes that the analysis of government and government policy needs to be based on a comparative institutional approach involving an assessment of institutional structures according to the processes and outcomes they involve, utilising generally accepted criteria for making social choices. Key factors that must be considered in comparing alternative means for achieving social goals are identified.